Florística, estrutura e guildas da comunidade arbóreo-arbustiva de um fragmento de Mata Atlântica no município de Socorro, SP - Sartori, Richieri Antônio (2010)
The intense progress of urban and agricultural needs led to the Atlantic Forest, one of the most important biomes in the world for its high biodiversity, was reduced to forest fragments, with varying degrees of isolation, size and shape. These are extremely important, because they represent all the genetic reserves of this biome and still are heavily threatened by several factors. The objectives of this study was to understand the structure and floristic composition, and their correlation with soil conditions. Also some ecological factors such as the proportion of species and individuals of the syndromes of dispersal of species, ecological classes, edge effect and to verify the patterns of distribution of diameter classes for the populations of the tree-shrub of a fragment of Atlantic Forest in the city of Socorro , SP (32'50' ° 22'S and 46 ° 34'18''W). For the survey 25 plots were randomly assigned (20 x 20 m each), totaling an area of 1 ha study in an area of 10 ha of lower montane semideciduous forest, and sampled all individuals living with diameter at breast height ( DAP) (1.3 m) greater than or equal to 5 cm. The species were classified in relation to dispersal syndromes in animal dispersed species, and anemochoric autochoric in relation to class eco-pioneer, early secondary, late secondary and climax. Variables were obtained from soil chemical and physical analysis of samples collected from each plot and the classification of soil types. 166 species belonging to 103 genera and 41 families were found. The community had density 1360 individual.ha-1 and basal area of 30.83 m2.ha-1, being more representative families Fabaceae with 30 species and Myrtaceae (25), gender, Eugenia, with 9 species and Ocotea ( 7), and species Eugenia pleurant and E. florida. The diversity index of Shannon was 3.95 and evenness was 0.79. 32 plots wind dispersed species (209 individuals), 19 autochoric (104) and 115 dispersed (1047) were found. The number of species was dispersed than expected. The ecological classes were represented by 43 pioneer species (208 individuals) 62 early secondary (321 individuals), 46 late successional (724 individuals) and 15 climax species (107 individuals). The study of edge effects showed that the distance of 30 meters there was an increase of pioneering individuals and decreased secondary. In dispersal syndrome and changes in distance of 30 meters, with a large reduction in animal-dispersed individuals and increased anemochoric.This analysis shows that the edge is the arrival of individuals more easily by wind and pioneers. A canonical correspondence analysis was significant, indicating that soil properties are interfering in the distribution of species in the area. The fragment presented similar to other fragments of semi deciduous forest in relation to structure and floristic.